Flame imaging using laser - based transmission tomography - Mohamad, Elmy Johana (2005)
This project describes an investigation of a flame imaging system using Laser- Based Tomography. The main purpose is to obtain the concentration profile of the flame to be incorporated in Laser-based transmission tomography measurement system for combustion on-line monitoring. The system can be applied to produce cross sectional images of flame such as that in a combustion chamber. Such a system can be employed to compare the effectiveness of different fuel additives and to monitor the onset of knock with various fuel formulations or cylinder head geometries. The ability to monitor the size, position and velocity of flame fronts in any combustion behavior and emissions. The concentration of this project is to determine the position and velocity of flame fronts in the pipeline by using photodiode (BPX 65) as sensor and Helium Neon Laser as laser sources. Laser will emit to pipe and the emitted light will strike to the photodiode through optical fiber as carry the laser light sources. To completely expand the laser light, the emitted light will collimated by a lens as is passes through the pipe walls. The system employs two orthogonal projections with one laser source. The laser source will supply 12 light beams, so the cross section of the pipe being interrogated by a total of 12 beams. In this case, we assume that the flame is placed in specific places in the measurement cross section and voltage output will calculated by the individual sensor is modeled. Besides the hardware, this project will include an interface user friendly, Visual C++ to visualize the concentration profile of the flame